Factors influencing physician risk estimates for acute cardiac events in emergency patients with suspected acute coronary syndrome. Issue 1 (12th November 2019) - Greenslade, Jaimi H; Sieben, Nicolas; Parsonage, William A; Knowlman, Thomas; Ruane, Lorcan; Than, Martin; Pickering, John W; Hawkins, Tracey; Cullen, Louise
Abstract : Background: Emergency physicians frequently assess risk of acute cardiac events (ACEs) in patients with undifferentiated chest pain. Such estimates have been shown to have moderate to high sensitivity for ACE but are conservative. Little is known about the factors implicitly used by physicians to determine the pretest probability of risk. This study sought to identify the accuracy of physician risk estimates for ACE in patients presenting to the ED with chest pain and to identify the demographic and clinical information emergency physicians use in their determination of patient risk. Methods: This study used data from two prospective studies of consenting adult patients presenting to the ED with symptoms of possible acute coronary syndrome. ED physicians estimated the pretest probability of ACE. Multiple linear regression analysis was used to identify predictors of physician risk estimates. Logistic regression was used to determine whether there was a correlation between physicians' estimated risk and ACE. Results: Increasing age, male sex, abnormal ECG features, heavy/crushing chest pain and risk factors were correlated with physician risk estimates. Physician risk estimates were consistently found to be higher than the expected proportion of ACE from the sampled population. Conclusion: Physicians systematically overestimate ACE risk. A range of factors are associated with physician risk estimates. These include factors strongly predictive of ACE, such as age and ECG characteristics. They also include other factors that have been shown to be unreliable predictors of ACE in an ED setting, such as typicality of pain and risk factors.